ATTITUDE OF INDONESIAN MUSLIMS TOWARDS PRODUCT BOYCOTT PRO-ISRAEL Analysis Of Fatwas Indonesian Ulema Council (MUI) Number 83 of 2023 Concerning Legal Status of Supporting the Palestinian Struggle - Fajri, Ibrahim; Rosyadi, Abdu Rahmat (Universitas Syiah Kuala, 2024)
This study investigates the Indonesian Ulema Council Fatwa Number 83 of 2023 concerning the Legal Status of Supporting the Palestinian Struggle, aiming to evaluate public compliance with the fatwa in boycotting Israeli products and their affiliates. The Indonesian Ulema Council, an independent Islamic organization not affiliated with any political parties or specific Islamic sects, possesses the authority to issue fatwas grounded in Sharia law. Through a qualitative juridical-sociological approach, this study scrutinizes the content and ramifications of these fatwas on the Muslim community in Indonesia. The research concludes that while MUI fatwas carry informal legal significance, their implementation should consider fundamental needs and national economic repercussions. Indonesian Muslims demonstrate diverse reactions to the fatwa, with some adhering to it due to religious beliefs, while others prioritize practical necessities and business concerns over the boycott call. The prevalent support for the fatwa must be considered in the pursuit of justice for Palestinians.